Screening of Donated Blood for Transfusion Transmitted Infections by Serology and Response Rate to Notification of Reactive Results: A Tertiary Care Institutional Experience - Bhalara, Rohit Vasantbhai; Shah, Payal; Kothari, Ravi Kiritkumar; Dhruva, Gauravi (Annals of Pathology and Laboratory Medicine, 2021)
Background: Safety for blood Transfusion begins with healthy donors. A basic part of preventing transfusion transmitted infections (TTIs) is to notify and counsel reactive donors. This study analysed trends in the prevalence of transfusion-transmissible infectious pathogens among blood donors and notify them as well as to assess response rate among them. Donor notification and counselling protect the health of the donor and stop secondary transmission of infectious diseases. Methods: 38707 blood donations were screened for TTIs, namely, HIV, HBV, HCV, and syphilis, Malarial Parasite by serology. ELISA testing for anti-HIV antibody, anti-HCV antibody and HBsAg and RPR test for syphilis, Rapid card test for Malarial Parasite. All reactive donors were retested in duplicate and notified of their status by communicating through telephone. Result: We evaluated 341 (0.88%) cases with reactive screening test results (0.617% HBV, 0.016% HCV, 0.134% HIV, 0.08% syphilis, 0.031% Malaria ). Only 179 donors (52.5%) responded to notification. The response among voluntary donors was better as compared to the replacement donors (54.1 % versus 40.7 %). Only 101 (57.22%) responsive donors followed their first attendance at referral clinic. Conclusion: Our study provides prevalence rate of TTIs among blood donors and importance of proper donor counselling and notification of TTI status to all reactive donors who opt to receive this information.